Annual Herbaceous Plants Exhibit Altered Morphological Traits in Response to Altered Precipitation and Drought Patterns in Semiarid Sandy Grassland, Northern China - Sun, Shan-Shan; Liu, Xin-Ping; Zhao, Xue-Yong; Medina-Roldánd, Eduardo; He, Yu-Hui; Lv, Peng; Hu, Hong-Jiao (Frontiers in Plant Science, 2022)
The frequency and intensity of extreme precipitation events and severe drought are predicted to increase in semiarid areas due to global climate change. Plant morphological traits can reflect plant responses to a changing environment, such as altered precipitation or drought patterns. In this study, we examined the response of morphological traits of annual herbaceous species to altered precipitation treatments in a semiarid sandy grassland. The study involved a control treatment (100% of background precipitation) and the following six altered precipitation treatments: (1) P(+): precipitation increased by 30%, (2) P(++): precipitation increased by 60%, (3) P(-): precipitation decreased by 30%, (4) P(--): precipitation decreased by 60%, (5) drought 1 (D1): 46-day drought from May 1st to June 15th, and (6) drought 2 (D2): 46-day drought from July 1st to August 15th. P(+) and P(++) increased the morphological traits of root, stem, leaf and reproductive meristems in the plant growing seasons, including the number of first-level root branches, root length, and root diameter. P(-) and P(--) decreased these morphological traits. The annual herbaceous plants markedly increased the number of second-level stem branches and stem and leaf diameters in order to better resist the severe drought stress. D1 remarkably decreased the fruit/seed length-to-width ratio and fruit/seed number, which would influence seed survival and propagation in the semiarid sandy grassland. Altered precipitation treatments affected the root-to-shoot ratio, which reflects biomass allocation to the belowground and aboveground parts. P(+) and P(++) increased the root, stem, leaf, and flower dry weight, with the flower dry weight accounting for a larger proportion than the other aboveground parts. Under D2, the plants used the limited water resources more efficiently by increasing the root-to-shoot ratio. A redundancy analysis showed that the root-to-shoot ratio and the dry weight of various plant components were significantly affected by morphological traits and altered precipitation magnitude. Our results showed that the herbaceous species have evolved morphological trait responses that allow them to adapt to climate change. Such differences in morphological traits may ultimately affect the growing patterns of annual herbaceous species, enhancing their drought-tolerant capacity in semiarid sandy grassland during the ongoing climate change.